DIPLOMASI EKONOMI INDONESIA TERHADAP PENINJAUAN ULANG SPECIAL SAFEGUARD (SSG) YANG DITERAPKAN FILIPINA PADA PRODUK KOPI INSTAN INDONESIA (2018) - Ester Desi Natasya (2020)
This study aims to analyze how Indonesia's economic diplomacy is to review the special safeguards applied by the Philippines on Indonesian instant coffee products. The problem of SSG is a problem for countries that export products. That is because SSG problems have an impact on the export market of Indonesian instant coffee products in the span of August to December 2018. This study uses descriptive methods and qualitative research types. Indonesia carried out a series of economic diplomacy through investments and imports of Philippine agricultural products to encourage the Philippines to withdraw its SSG policy which harmed Indonesia's instant coffee export products. Various meetings of high level officials at the ministry level were held to conduct discussions and meetings. In the results of economic diplomacy, Indonesia succeeded in encouraging the Philippines to review and reopen the export market of Indonesia's instant coffee products.